Dance in West Africa: Analysis and Description in Relation to Aspects of Communication Theory - van Niekerk, Heather (International Library of African Music, 2020)
pages: 175-177
Keywords: West Africa; Book reviews; West African Dance; Communication Theory; Cultural Analysis; African Music